Transient Viral Rebound in Children with Perinatally Acquired HIV-1 Induces a Unique Soluble Immunometabolic Signature Associated with Decreased CD4/CD8 Ratio. Issue 3 (2nd February 2023) - Tarancon-Diez, Laura; Peraire, Joaquim; Jiménez de Ory, Santiago; Guirro, Maria; Escosa, Luis; Prieto Tato, Luis Manuel; Penín Antón, María; Piqueras, Ana Isabel; Vázquez Pérez, Álvaro; Gavilán, César; Bustillo-Alonso, Matilde; Navarro, María Luisa; et al.
Abstract: Background: To determine by multi-omic analysis changes in metabolites, lipids, and proteins as a consequence of transient viral rebound (tVR) in children with perinatally acquired HIV-1 (PHIV). Methods: Plasma samples from children with PHIV and with tVR (first episode of transient RNA-HIV viral load >20 copies/ml followed by suppression) on the time-point immediately before (pre-tVR) and after (post-tVR) the tVR were assessed. Multi-omic analyses were performed using nLC-Orbitrap, GC-qTOF-MS, and LC-qTOF-MS. Results: Comparing pre- and post-tVR time-points, HIV-1 children with tVR ( n = 5) showed a trend to a decrease in ratio CD4/CD8 ( p = 0.08) but no significant differences were observed in plasma metabolites, lipids, or proteins. Post-tVR condition was compared with a reference group of children with PHIV with persistent viral control ( n = 9), paired by sex, age, and time under antiretroviral treatment. A total of 10 proteins, 8 metabolites, and 2 lipids showed significant differences ( p < 0.05): serotransferrin, clusterin, kininogen-1, succinic acid, threonine, 2-hydroxyisovaleric acid, methionine, 2-hydroxyglutaric, triacylglyceride 50:0 (TG50:0), and diacylglyceride 34:1 (DG34:1) were upregulated while alpha-2-macroglobulin, apolipoprotein A-II, carboxylic ester hydrolase, apolipoprotein D, coagulation factor IX, peptidase inhibitor 16, SAA2-SAA4 readthrough, oleic acid, palmitoleic acid, and D-sucrose downregulated on post-tVR time-point compared to the reference group. Ratio CD4/CD8 correlated with apolipoprotein A-II, DG34:1, and methionine ( p = 0.004; ρ = 0.71, p = 0.016; ρ = −0.63; and p = 0.032; ρ = −0.57, respectively). Nadir CD4+ correlated inversely with kininogen-1 ( p = 0.022; ρ = −0.60) and positively with D-sucrose ( p = 0.001; ρ = 0.77). Conclusions: tVR followed by suppression implies changes in soluble proteins, lipids, and metabolites that correlate with immunological parameters, mainly ratio CD4/CD8, that decreased after tVR. These distinct soluble biomarkers could be considered potential biomarkers of immune progression. Abstract : Transient loss of HIV-viral control followed by suppression deals with significant changes in soluble proteins, lipids, and metabolites that correlate with immunological parameters. The distinct soluble biomarkers found could be considered potential biomarkers of immune progression.